The reproductive biology of Spondyliosoma cantharus (L.) from the SW Coast of Portugal - J. M.S. Gonçalves (Scientia Marina, 2000)
The study of Spondyliosoma cantharus (L.) reproduction was carried out within the framework of a project on the fisheries resources of the south-west coast of Portugal, and was based on the analysis of the spawning season, gonad maturation, size-at-maturity, fecundity, and hermaphroditism. Spawning took place from February to April, peaking in March. Analysis of the sex ratio by size class and season showed that females were more abundant throughout the year (M/F=0.57) and in the smaller size classes. Overall size at first maturity (L50) was 20.10 cm total length (TL), with a significant difference between males (22.41 cm, TL) and females (19.98 cm, TL). Absolute fecundity (Fa) ranged from 37,506 to 112,074 oocytes, with a mean of 61,396. A power type relationship best described the relationships between absolute fecundity and TL (Fa = 436.27TL1.575), and somatic weight (Fa = 2979.7SW0.585). The number of oocytes/g of female somatic weight ranged from 217 to 549, with a mean of 346. The reproductive strategy of this species is characterised by protogynic hermaphroditism, as indicated by the presence of individuals in transition and of testes with vestiges of preceding ovaries associated with the significant differences in the size frequency distributions of the sexes.